Los liberalismos de Argentina, Brasil y Uruguay ante el enigma peronista (1943-1955) - Ernesto Bohoslavsky (Centre de Recherches sur les Mondes Américains, 2016)
For a long time, Latin America has been considered a hopelessly populist land. This very essentialized and comprehensive academic and political characterizations on the continent disowns the power of anti-populist actors. This paper aims to reconstruct the behavior and speechs of some of the anti populist coalitions as well as those of liberal politicians in Argentina, Brazil and Uruguay in the peronist scenario. This work provides some evidence on mutual perceptions and cooperation among national actors from a transnational history approach; and portrays the collective imagination and the republican, anti-fascist and in some cases, elitist political culture shared by antiperonist Argentine leaders, as well as those of the UDN in Brazil and of Batllism in Uruguay. This perspective was shaped by the denunciation and the critique on what has been reported as “populist” practices - demagogic and empty rhetoric, irresponsible public expenditure and political manipulation.Since politicians in Argentina, Brazil and Uruguay have held political, personal and intellectual bonds stated in newspapers, letters and public speeches, it is easy to identify joint features and ties across frontiers. They have understood -and intervened in- the political life keeping an eye on the political situation of the neighboring country in an effort to build an anti populist South American coalition in the transition between the end of WW2 and the beginning of the Cold War.